Pengaruh Beban Kerja dan Lingkungan Kerja Terhadap Turnover Intention pada Karyawan Honda Gajah Motor Cabang Khatib Sulaiman Padang - Zusmawati, Zusmawati; Alisah, Delima Regiyani (Lembaga Yasin AlSys, 2025)
The high level of turnover intention in the automotive sector, especially in motorcycle dealerships, is a serious challenge for human resource management. This study aims to examine the effect of workload and work environment on turnover intention in Honda Gajah Motor Padang employees. This study uses a quantitative approach with a sample size of 165 employees selected through total sampling technique. The instrument used is a closed questionnaire in the form of a Likert scale, and the data collected is primary data. Data analysis techniques include validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing, with the help of the latest version of the SPSS program. The results showed that partially workload and work environment have a positive and significant effect on employee turnover intention. Thus, it can be concluded that high workload and non-conducive work environment contribute to the increasing intention of employees to leave the company. This research provides practical implications for management in designing workload management strategies and improving the quality of the work environment to reduce turnover intention.